Learning Autodesk® Maya® 2008 : (Autodesk, 2007)
Learning Autodesk Maya 2008 I Foundation is your key to unlocking the power of Autodesk Maya software, directly from the creators of one of the world's most powerful 3D animation and effects software products. Get hands-on experience with the innovative tools and powerful techniques available in Autodesk Maya 2008. You'll gain a sense of the entire production process as you work on creating and animating characters from Sony Pictures Animation's feature film, Surf's Up. You'll even learn about compositing your characters into alternate environments in a bonus chapter on Autodesk Combustion software. Explore the Maya user interface, create organic structures with NURBS, apply forward and inverse kinematics, deform surfaces, learn to use Trax non-linear animation, discover rendering techniques, and so much more with this easy to follow guide to Maya. Includes bonus DVD with scene files, instructor-led podcasts, and other reference guides to give you a solid foundation in the art of animating with Maya.